"Tax Discrimination District": The Intersection of Race and Transit Value Capture. Issue 3 (3rd July 2022) - Fischer, Lauren Ames
Abstract: Problem, research strategy and findings: Recent efforts to promote land value capture as a solution to the fiscal crisis of local governments have gained traction, increasing the use of value capture tools across a variety of contexts. This research provides a case study examining how the politics of transit value capture district designation intersect with racialized patterns of disinvestment. Using the case of Kansas City (MO), I illustrate how the attempts of planners and policymakers to expand transit value capture were met with resistance from both low-income and wealthy neighborhoods. I explore how differentiated response to neighborhood concerns by planners combined with stakeholder frameworks about social equity and perceptions of historical domination to produce results exactly counter to the stated purpose of "not building transit purely for the White people." The case illustrates the importance of considering racial inequities and historic patterns of marginalization in transit value capture to achieve racial equity and challenge existing patterns of segregation. Takeaway for practice: Designating value capture district boundaries is a sociotechnical process that interacts with and potentially reinforces existing patterns of domination and oppression. To ensure that value capture implementation does not reproduce and exacerbate existing inequities, urban planning professionals should centralize issues of race, segregation, and marginality in their efforts to create, capture, and distribute land value. Value capture schemes need to be tailored to the local built environment, sociodemographic history, and the needs of specific communities to be effective at addressing spatial inequities.